2017
DOI: 10.23736/s0022-4707.16.06019-9
|View full text |Cite
|
Sign up to set email alerts
|

Geographic enrolment of the top 100 in athletics running events from 1996 to 2012

Abstract: +33141744124Purpose It is widely accepted in the literature that athletes of West African origins achieve the best sprint performances; while, athletes originating from East Africa are the most efficient at long distances. No epidemiological studies have measured the evolution of the contributing of each of these athlete origin groups from 100m to the marathon.Method Speed, morphology and geographic origin of the Top 100 male and female athletes (from 100m to the marathon) were collected and analyzed over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The observed results are in line with previous studies that compared female long-distance runners and non-athletes [9,33]. In addition, while the present study assessed university athletes, their body sizes and calculated BMIs were comparable to those of elite long-distance runners of different ethnic backgrounds [6,9,10]. While a relatively small sample size contributed to the results, consistent results with previous studies indicate the possibility of increasing body size among…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed results are in line with previous studies that compared female long-distance runners and non-athletes [9,33]. In addition, while the present study assessed university athletes, their body sizes and calculated BMIs were comparable to those of elite long-distance runners of different ethnic backgrounds [6,9,10]. While a relatively small sample size contributed to the results, consistent results with previous studies indicate the possibility of increasing body size among…”
Section: Discussionsupporting
confidence: 92%
“…While the associations between body mass or BMI and performance have not been confirmed in long-distance running to date, female runners in particular are reported to have a lower BMI [6,7] than male runners [3,5,6,8] and often have BMIs that are considered "underweight" (i.e., below 18.5 kg/m 2 ) [9,10] according to the classification of the World Health Organization (WHO) [11]. Excessive concern about weight and preoccupation with weight loss among female long-distance runners may be associated with distorted body image.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the country of origin of long-distance triathletes, it has been reported that most finishers, as well as the fastest athletes competing in ‘Ironman ® Hawaii’, originated from the United States of America [ 7 ]. Although the previous literature has showed the dominance of certain nations in specific sports disciplines [ 4 , 6 , 8 , 9 ], little evidence is available regarding the place of competition or if these characteristics are performance-related. As the most popular long-distance triathlon in the world, athletes travel hundreds of miles to compete in Ironman ® 70.3 events, with many travelling thousands of miles to compete at remote locations and achieve personal goals or to earn a spot in the World Championship.…”
Section: Introductionmentioning
confidence: 99%